Razón y Revelación en la Edad Media: la Primacía de la Fe - Ceferino Muñoz Medina (Studia Gilsoniana)
This paper analyzes, from a historical-philosophical perspective inspired by Étienne Gilson, the various attitudes adopted by medieval Christian thinkers toward the tension between reason and revelation. Through a typology that distinguishes two major “spiritual families” –the Tertullian and the Augustinian– the text reconstructs the main medieval positions regarding theological knowledge and its relationship with philosophy. The Tertullian family, paradigmatically represented by figures such as Tertullian, Tatian, and Peter Damian, upholds a radical distrust of natural reason and defends the absolute self-sufficiency of Christian revelation as the sole and exclusive source of truth. In contrast, the Augustinian family –whose founding figure is Saint Augustine and which includes authors like Saint Anselm, Roger Bacon, and Ramon Llull– proposes a positive articulation between faith and reason, based on the premise that revealed truth can and must be the object of rational inquiry. This line of thought, while preserving the primacy of faith, affirms the illuminating role of reason in deepening the Christian mystery. The text suggests that these two attitudes not only coexisted throughout the Middle Ages but also offer interpretative keys for understanding the later development of Christian philosophy. In doing so, it challenges the reductive image of the Middle Ages as a dark age, revealing instead its internal complexity and enduring relevance in the ongoing dialogue between theology and philosophy.